2020
DOI: 10.1093/cdn/nzaa120
|View full text |Cite
|
Sign up to set email alerts
|

Food Insecurity Is Associated with Increased Risk of Obesity in US College Students

Abstract: Background Food insecurity affects millions of Americans and college students are especially vulnerable. Little is known about the relationship of food insecurity with weight status and dietary intake during this critical phase of emerging adulthood. Objectives To examine the sex-specific associations of food insecurity with obesity and dietary intake. The study also explored these associations by meal plan (MP) enrollment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 36 publications
1
25
1
Order By: Relevance
“…Lastly, the relatively small sample size of this study may not have been adequate to capture all potential differences between food-secure and food-insecure students. For example, food insecurity was not associated with BMI or body fat percentage in this study, though many previous studies have found food insecurity to be associated with obesity [24,37,[40][41][42].…”
Section: Discussioncontrasting
confidence: 90%
“…Lastly, the relatively small sample size of this study may not have been adequate to capture all potential differences between food-secure and food-insecure students. For example, food insecurity was not associated with BMI or body fat percentage in this study, though many previous studies have found food insecurity to be associated with obesity [24,37,[40][41][42].…”
Section: Discussioncontrasting
confidence: 90%
“…Serious ethical and health-related issues hinder healthcare providers working with vulnerable populations. In general, differences in weight status and dietary intake reveal that a trend in obesity increases as the degree of food insecurity increases (103) . The COVID-19 crisis has highlighted food insecurity as a significant factor in nutritional poverty (97) .…”
Section: Determinants That Can Influence Body Weight During Pandemicsmentioning
confidence: 99%
“…Food insecurity among college students has become an active topic of investigation. A study analyzing obesity in 683 second year students from eight US universities found food-insecure students had a significantly higher BMI than food-secure students (26.0 kg/m [ 2 ] ± 0.4 compared with 24.2 kg/m [ 2 ] ± 0.1, P = 0.001) [ 16 ]. Food insecurity was significantly associated with obesity in both men (OR 3.84; 95% Cl: 1.47, 10.02) and women (OR 2.88, 95% Cl: 1.46, 5.71) after adjusting for demographic characteristics.…”
Section: Resultsmentioning
confidence: 99%